Chemical Fingerprints of Honey Fermented by Conventional and Non-Conventional Yeasts - Dorota Kregiel; Urszula Dziekonska-Kubczak; Karolina Czarnecka-Chrebelska; Katarzyna Pielech-Przybylska (Molecules)
Previous studies have shown the positive effects of non-conventional Metschnikowia spp. yeasts in mixed cultures with Saccharomyces cerevisiae on the properties of fruit wines. In this study, we investigated the effects of using conventional S. cerevisiae and non-conventional Metschnikowia pulcherrima yeasts as starter cultures in controlled mixed fermentations of honey wort. Other non-conventional yeasts were also tested for comparison, including Wickerhamomyces anomalus, Dekkera/Bretannomyces bruxellensis, and Wickerhamomyces anomalus. We evaluated the tolerance of the tested yeasts to high sugar content and analyzed the metabolic profiles of both monocultures and mixed systems. The M. pulcherrima strain showed the highest tolerance to 30% w/v glucose. The chemical complexity of fermented honey was improved using M. pulcherrima in co-starters with S. cerevisiae. The fermented honey samples were characterized by lower ethanol content, higher glycerol level, and rich volatilomes containing higher levels of both esters (ethyl acetate, 3-methylbutyl acetate, 2-methylpropyl acetate) and aliphatic alcohols (2-methylpropan-1-ol, 3-methylbutan-1-ol, and 2-methylbutan-1-ol). Similar characteristics were obtained using mixed populations of four strains: S. cerevisiae, M. pulcherrima, D. bruxellensis, and W. anomalus.